Genetic stratigraphy of key demographic events in Arabia - Fernandes, Verónica; Triska, Petr; Pereira, Joana B; Alshamali, Farida; Rito, Teresa; Machado, Alison; Fajkošová, Zuzana; Cavadas, Bruno; Černý, Viktor; Soares, Pedro; Richards, Martin B; Pereira, Luísa (PloS one, 2015)
At the crossroads between Africa and Eurasia, Arabia is necessarily a melting pot, its peoples enriched by successive gene flow over the generations. Estimating the timing and impact of these multiple migrations are important steps in reconstructing the key demographic events in the human history. However, current methods based on genome-wide information identify admixture events inefficiently, tending to estimate only the more recent ages, as here in the case of admixture events across the Red Sea (~8-37 generations for African input into Arabia, and 30-90 generations for "back-to-Africa" migrations). An mtDNA-based founder analysis, corroborated by detailed analysis of the whole-mtDNA genome, affords an alternative means by which to identify, date and quantify multiple migration events at greater time depths, across the full range of modern human history, albeit for the maternal line of descent only. In Arabia, this approach enables us to infer several major pulses of dispersal between the Near East and Arabia, most likely via the Gulf corridor. Although some relict lineages survive in Arabia from the time of the out-of-Africa dispersal, 60 ka, the major episodes in the peopling of the Peninsula took place from north to south in the Late Glacial and, to a lesser extent, the immediate post-glacial/Neolithic. Exchanges across the Red Sea were mainly due to the Arab slave trade and maritime dominance (from ~2.5 ka to very recent times), but had already begun by the early Holocene, fuelled by the establishment of maritime networks since ~8 ka. The main "back-to-Africa" migrations, again undetected by genome-wide dating analyses, occurred in the Late Glacial period for introductions into eastern Africa, whilst the Neolithic was more significant for migrations towards North Africa.
Keywords: Founder Effect; tok genů; Arabia; Gene Flow; DNA, Mitochondrial; Afrika; History, Ancient; Genomics; Human Migration; lidé; Phylogeny; Arábie; efekt zakladatele; Africa; Haplotypes; mitochondriální DNA; dějiny starověku; Principal Component Analysis; demografie; analýza hlavních komponent; haplotypy; migrace lidstva; fylogeneze; Demography; genomika; Humans